Faktor-faktor yang Mempengaruhi Minat Masyarakat dalam Mengeluarkan Zakat Melalui Badan Amil Zakat Nasional (BAZNAS) di Kota Mataram - Auugerah Ayu; Moh. Huzaini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Zakat is one of the pillars of Islam; where if all Muslims have assets that exceed the nisab limit, they are obliged to pay zakat to comply with religious teachings and to cleanse their assets of things that are haram to achieve the blessing of Allah SWT. Zakat is also an asset determined to make humanitarian contributions and valid for a long time. This study aims to analyze the influence of trust, income, transparency and religiosity, moderated by the public interest in paying zakat at BAZNAS Mataram City. This study used quantitative research and an associative approach, where non-probability sampling through a purposive sampling approach was implemented in the data collection of this study. The respondents were determined to 100 respondents. This study uses primary data, whose data is collected through questionnaires or questionnaires. After that, Structural Equation Modeling (SEM) was implemented in the data analysis with the help of SmartPLS 4.0 software. This study showed the results that indicate that trust and religiosity have a positive and significant effect on people's interest in paying zakat at BAZNAS Mataram City. In contrast, income and transparency have a positive impact, although not substantial, on people's interest in paying zakat at BAZNAS Mataram City, while trust, income, and transparency moderated by religiosity these three variables have a positive effect. However, trust only significantly affects people's interest in paying for zakat at the National Zakat Agency of Mataram City.